2007
DOI: 10.1007/s00221-007-0885-4
|View full text |Cite
|
Sign up to set email alerts
|

Visual memory capacity in transsaccadic integration

Abstract: How we perceive the visual world as stable and unified suggests the existence of transsaccadic integration that retains and integrates visual information from one eye fixation to another eye fixation across saccadic eye movements. However, the capacity of transsaccadic integration is still a subject of controversy. We tested our subjects' memory capacity of two basic visual features, i.e. luminance (Experiment 1) and orientation (Experiment 2), both within a single fixation (i.e. visual working memory) and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 133 publications
10
82
0
Order By: Relevance
“…First, visual stability is not as absolute as introspection would lead us to believe. Stability is preserved only for a limited number of attended objects [26,31,32,77], which is sufficient since those objects guide action and conscious perception [14]. The feeling that we have a complete and stable perception of the entire visual field has been called a 'grand illusion' [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, visual stability is not as absolute as introspection would lead us to believe. Stability is preserved only for a limited number of attended objects [26,31,32,77], which is sufficient since those objects guide action and conscious perception [14]. The feeling that we have a complete and stable perception of the entire visual field has been called a 'grand illusion' [16].…”
Section: Resultsmentioning
confidence: 99%
“…In order to be integrated across saccades, stimuli need to be stored in TSM. Rather than a dedicated mechanism for trans-saccadic perception, TSM appears to rely on working memory [26,31]. TSM has a limited capacity and only information about attended stimuli is retained [31,32].…”
Section: Trans-saccadic Memorymentioning
confidence: 99%
“…The experimental procedure is similar to one previously described in detail previously (Prime et al, 2007b), but used TMS to investigate the putative neural mechanisms underlying transsaccadic memory. Briefly, as illustrated in Figure 2, the transaccadic memory task required subjects to compare the orientation of a postsaccadic probe relative to the orientation of a presaccadic target at the same location, usually among similar-looking presaccadic distracters.…”
Section: Methodsmentioning
confidence: 99%
“…This process of retaining visual information across saccades is transsaccadic memory. Various studies have shown that transsaccadic memory has a capacity of three to four items (Irwin and Andrews, 1996;Irwin and Gordon, 1998;Prime et al, 2007b); similar to visual working memory (Luck and Vogel, 1997;Vogel et al, 2001). However, transsaccadic memory involves additional computational demands the visual system must solve, which distinguishes itself from visual working memory, such as the egocentric measures of saccade metrics so that the spatial information of objects retained in transsaccadic memory is updated in accordance to the saccade (Hayhoe et al, 1991;Prime et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation